A Companion to Nordic Cinema - Hjort, Mette and Lindqvist, Ursula (John Wiley & Sons Ltd, 2021)
A Companion to Nordic Cinema presents a collection of original essays that explore one of the world's oldest regional cinemas from its origins to the present day. -- Offers a comprehensive, transnational and regional account of Nordic cinema from its origins to the present day -- Features original contributions from more than two dozen international film scholars based in the Nordic countries, the United States, Canada, Scotland, and Hong Kong -- Covers a wide range of topics on the distinctive evolution of Nordic cinema including the silent Golden Age, Nordic film policy models and their influence, audiences and cinephilia, Nordic film training, and indigenous Sámi cinema. -- Considers Nordic cinema's engagement with global audiences through coverage of such topics as Dogme 95, the avant-garde filmmaking movement begun by Danish directors Lars von Trier and Thomas Vinterberg, and the global marketing and distribution of Nordic horror and Nordic noir -- Offers fresh investigations of the work of global auteurs such as Carl Th. Dreyer, Ingmar Bergman, Lars von Trier, Aki Kaurismäki, and Roy Andersson. -- Includes essays on Danish and Swedish television dramas, Finland's eco-documentary film production, the emerging tradition of Icelandic cinema, the changing dynamics of Scandinavian porn, and many more
https://katalog.adlr.link/Record/51-9781119239109